THE CORRELATION OF WAIST HIP RATIO TO ISCHEMIC STROKE PROBABILITY OF POPULATION IN SEKARBELA MATARAM - Setiadi, Qisthinadia Hazhiyah; Harahap, Herpan Syafii; Indrayana, Yanna (Malang Neurology Journal, 2018)
Background. Stroke is the third cause of death worldwide. Ischemic stroke is the most common type of stroke with high prevalence. Obesity is one of ischemic stroke risk factor, but its correlation with higher ischemic stroke risk remains unclear. Studies about correlation of waist hip ratio (WHR) and ischemic stroke risk is still contradictive. Objective. This study was aimed to explore the correlation between WHR and ischemic stroke probability.Methods. This was a descriptive analytic study using cross sectional design. The population of this study was resident in Sekarbela Mataram aged 55-84 years old. This study was conducted 63 participants. They were interviewed and received a measurement of WHR and ischemic stroke probability. The ischemicstroke probability was assessed by using assessment of Framingham stroke risk score. Data were analyzed by using Pearson correlation.Results. Among 63 participants, 51 (81%) were abdominal obesity and 12 (19%) were normal based on WHR measurement. Pearson correlation analysis showed that there was no correlation between WHR and ischemic stroke probability (p = 0,11).Conclusion. There was no correlation between WHR and ischemic stroke probability of population in Sekarbela Mataram